Improvement of otoendoscopic surgery for epitympanic cholesteatoma invading the mastoid. (3rd June 2019) - Wu, Nan; Wang, Fangyuan; Hou, Zhaohui; Yang, Shiming
Abstract: Background: In recent years, the otoendoscopic surgery for epitympanic cholesteatoma has achieved great development, but it still has some disadvantages. Objective: This work aims to improve otoendoscopic surgery for epitympanic cholesteatoma invading the mastoid to retain the normal structure of the middle ear as much as possible. Methods: We classified the patients according to the lesion scope and applied different strategies of using the combination of otoendoscope and microscope. The surgery was improved and the recurrence and residual of middle ear cholesteatoma after operation were observed preliminarily. Results: Forty-six patients with middle ear cholesteatoma accepted surgical treatment, including 10 cases of independent otoendoscopic surgery, 29 cases of otoendoscope–microscope combined surgery, and seven cases of microscopic surgery assisted with an otoendoscope. All cases were treated with canal-up cholesteatoma surgery. The postoperative recurrent rate was 4/46. Conclusion: We improved existing otoendoscopic surgery to reduce or avoid bony defects of the acoustic meatus, and then decreased the proportion of canal-down surgery.